Influence on Polyurethane Synthesis Parameters Upon the Performance of Base Asphalt - Jin, Xin; Sun, Siwei; Guo, Naisheng; Huang, Shuolei; You, Zhanping; Tan, Yiqiu (Frontiers in Materials, 2021)
The objective of this study aims to investigate the performance of thermoplastic polyurethane elastomers (TPU) modified asphalt, especially focus on the influence of polyurethane synthesis parameters upon the performance of base asphalt. In this study, the TPU modifier was incorporated into base asphalt to prepare TPU modified asphalt by using a self-determined laboratory process. The properties of polyester-based TPU and polyether-based TPU modified asphalt with different contents was analyzed by the base performance tests. The Fourier transform infrared spectroscopy (FTIR), fluorescent microscope, scanning electron microscopy (SEM), differential scanning calorimetry (DSC), thermal gravity (TG), dynamic shear rheology (DSR), and bending beam rheology (BBR) tests were conducted to expose chemical, microstructure and rheological properties of the asphalt binders, respectively. The results indicated that the modified asphalt with 5% TPU modifier exhibited a favorable performance in terms of the penetration, ductility, softening point and rotational viscosity, respectively. The isocyanate and polyol reacted to form carbamate in the TPU modified asphalt, and moreover the isocyanate and aromatic compounds reacted to form halohydrins in the asphalt. Large particles contained in the polyester-based TPU modified asphalt increased obviously with the increase of Ch and r value, the fracture mode of it subjected to external load indicated a typical brittle fracture. The content of MDI in the synthesized polyurethane modifier was an important factor affecting the high-temperature stability of the modified asphalt. The polyester-based TPU modifier performed better high temperature performance than the polyether-based TPU modifier. The polyether polyol chain segment showed a great flexibility as compared to polyester polyol, the addition of polyether polyols can be effectively offset of MDI chain rigidity as r ≤ 1 and Ch ＜ 40% leading to the improvement of the viscoelastic property of asphalt. When Ch = 40% and r = 0.95, the polyether-based TPU modified asphalt exhibited the same high-temperature grade as the polyester-based TPU modified asphalt, whereas the polyether-based TPU modified asphalt showed the obviously higher low temperature grade. The polyester-based TPU with Ch = 40% and r =1 can be used as modifier to increase the durability of asphalt binders.